1995
DOI: 10.1007/bf00118873
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of trap and skeet shooting targets to aquatic test species

Abstract: : Large quantities of trap and skeet clay targets are used in shooting activities around the United States. For example, the number of targets used since 1970 has averaged approximately 560 million a year. A number of acute and chronic tests were performed to determine the toxicity of Remington Arms Company Blue Rock(®) trap and skeet target fragments upon selected freshwater and marine organisms. These studies were undertaken in support of an environmental impact study of trap and skeet shooting activities at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The initial comprehensive literature review focused on clay target shooting revealed that there was a large volume of studies irrelevant to our purpose. For example, examining the environmental influence of lead pollution and the impact of the clay targets on the ecology at a shooting range (Baer et al, 1995;McTee et al, 2016;Migliorini et al, 2004;Rooney and McLaren, 2000;Sorvari et al, 2006;Vyas et al, 2000). Indeed, our review has indicated only one study by Puglisi et al (2014), focusing on the relationship between good balance and better performance in the skeet shooting discipline.…”
Section: Resultsmentioning
confidence: 99%
“…The initial comprehensive literature review focused on clay target shooting revealed that there was a large volume of studies irrelevant to our purpose. For example, examining the environmental influence of lead pollution and the impact of the clay targets on the ecology at a shooting range (Baer et al, 1995;McTee et al, 2016;Migliorini et al, 2004;Rooney and McLaren, 2000;Sorvari et al, 2006;Vyas et al, 2000). Indeed, our review has indicated only one study by Puglisi et al (2014), focusing on the relationship between good balance and better performance in the skeet shooting discipline.…”
Section: Resultsmentioning
confidence: 99%
“…Contamination of shooting range soils poses a risk of trace element accumulation to higher trophic levels. Considering high contamination in the shooting range soils, these sites' ecotoxicological risks of these sites become an important eld of study (Baer et al 1995 ). Contamination of hazardous trace elements results in a reduced of survival and reproduction rate of earthworms (Luo et al 2014a;Sanderson et al 2014), mites (Luo et al 2015), and negatively affects all soil faunal communities (Selonen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of shooting range soils poses a risk of trace element accumulation to higher trophic levels. Considering high contamination in the shooting range soils, these sites' ecotoxicological risks of these sites become an important eld of study (Baer et al 1995;Reid and Watson 2005;Sneddon et al 2009;Sanderson et al 2018; Sujetovienė and Česynaitė 2019; Dinake et al 2019). Contamination of hazardous trace elements results in a reduced of survival and reproduction rate of earthworms (Luo et al 2014a;Sanderson et al 2014), mites (Luo et al 2015), and negatively affects all soil faunal communities (Selonen et al 2014).…”
Section: Introductionmentioning
confidence: 99%